2001
DOI: 10.1016/s1201-9712(01)90043-8
|View full text |Cite
|
Sign up to set email alerts
|

Tropical diabetic hand syndrome: Risk factors in an adult diabetes population

Abstract: The major risk factors for the tropical diabetic hand syndrome are intrinsically related to the underlying disease. Thus, prevention of hand infections may require aggressive glucose control, and education on hand care and the importance of seeing a doctor promptly at the onset of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 9 publications
1
42
0
9
Order By: Relevance
“…This is linked to the responsibility of women for farming and planting crops in rural areas in Africa (40,41). Reviewing the literature, we found male dominance overall in subject ratio.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This is linked to the responsibility of women for farming and planting crops in rural areas in Africa (40,41). Reviewing the literature, we found male dominance overall in subject ratio.…”
Section: Discussionmentioning
confidence: 77%
“…The majority of reports related to hand infections in diabetes are from developing countries in the tropical world and it is defined as diabetic hand syndrome with musculoskeletal manifestations such as limited joint mobility, Dupuytren's contracture, and trigger fingers (10,11,(13)(14)(15)17,19,21,24,31,37,40,41). Diabetes and related complications are common in Turkey but only three studies about hand complications related to diabetes from this country were found in the literature (2,6,20).…”
Section: Discussionmentioning
confidence: 99%
“…unaware or even no trauma at all. 2,4,7 Our patient also did not recall any preceding trauma and could, if at all, have been just trivial of which she was unaware.…”
Section: Discussionmentioning
confidence: 82%
“…A significant incidence of diabetic hand infections have been reported in tropical regions, particularly Sub-Saharan Africa and the term coined for such infections has been denoted as tropical diabetic hand syndrome (TDHS). 2,4 TDHS is an aggressive type of hand sepsis that results in significant morbidity and mortality among patients of diabetes in the tropics. 10 TDHS has also been reported among diabetic patients in the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation